Vietnam’s international integration in science and technology with ASEAN countries towards sustainable development - Sinh, Bach Tan (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2018)
In order to meet the need for the increase in global integration process, ASEAN Summit in 2001 called for the establishment of the ASEAN Economic Community and on 31st December, 2015, ASEAN Economic Community was established. AEC is one of the three key pillars of the ASEAN community to achieve the goals set out in the ASEAN Vision 2020. The purposes of AEC are: (i) Enhancing the competitiveness of ASEAN, improving the investment environment of ASEAN, (ii) Narrowing the development gap between members and achieving a deeper economic integration in the region. AEC will be characterized by an unique market, a common production base with the free movement of goods, services, capital flows as well as the free movement of entrepreneurs and labor force, especially skilled workers. The vision of the ASEAN S&T community is to create a community of ASEAN S&T for contributing and sharing resources to enhance the region’s productivity through innovation activities. To achieve this vision, ASEAN pledged to link S&T programs and resources of member countries to improve efficiency in terms of increasing competitiveness in the region. This paper will provide the basic concepts and characteristics of international integration in S&T, analyze the international integration of S&T in Vietnam including achievements and limitations. The article will also propose a number of measures and mechanisms to enhance Vietnam’s international integration in S&T with ASEAN countries towards sustainable development. Code: 17053001